Los titanes y Noé: un ejemplo del sincretismo cultural de la comunidad judía de Alejandría - Nieto, Jesús M. (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 1991)
This essay aims to prove, by means of an illustrative example. the cultural syncretism existing in the Jewish community in Alexandria during the Hellenistic period and the first centuries of the imperial epoch. This cultural symbiosis is clearly reflected in the literature of this period, both in its formal aspects and in its contents. This essay specifically centres on some passages of the Sibilline Oracles where the Greek tale of Titanomachia mingles with the Biblical story of Noah merely for the purpose of propaganda of the principles of Jewish religion. All this is expressed in a mythological language invested with greater authority and acceptance in a .Jewish hellenized atmosphere.